Workplace Spirituality as School Performance Improvement in the Era of Society 5.0: A Review from an Organizational Behaviour Perspective - Hadi, Eka Putranto; Hidayah, Isti; Sutarto, Joko (Universitas Negeri Semarang, 2024)
In the era of society 5.0, increasingly advanced technological developments have an impact on schools, schools as organizations must be able to optimize to achieve performance, one of which is through spirituality in the workplace. Spirituality in the workplace can be used as a guideline or tool to influence in achieving good school performance improvements by integrating technological developments. Improved performance will be in line with good organizational behaviour, from this it can achieve school performance goals optimally. The purpose of this paper is to analysis workplace spirituality in improving school performance based on organizational behaviour. This writing method uses a literature review by searching for information from secondary sources, then comparing and analysis according to the objectives. The results of this writing are that schools need to adapt in the era of society 5.0 through workplace spirituality, workplace spirituality can provide increased school performance, including feeling meaningful, togetherness, and harmony with organizational values. While the role of spirituality in the workplace can provide a role and impact on school or organizational performance such as effectiveness, efficiency, productivity, innovation, quality of life and work morale.